1997
DOI: 10.1002/(sici)1096-8652(199709)56:1<5::aid-ajh2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced generation of monocyte tissue factor and increased plasma prothrombin fragment1+2 levels in patients with polycythemia vera: Mechanism of activation of blood coagulation

Abstract: Polycythemia vera (PV) is associated with a high incidence of thrombosis. The association of apparent and secondary polycythemia with thrombosis is not clear. It was suggested that activation of the coagulation system contributes to thrombus formation in PV. However, the mechanism of activation is unknown. Monocytes generate a potent tissue factor (TF) upon stimulation with various substances, which is involved in thrombus formation in various disorders. Therefore, we studied the possibility that the factor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
(42 reference statements)
1
18
1
Order By: Relevance
“…Obstructive sleep apnea (OSA), obesity hypoventilation syndrome, and chronic obstructive pulmonary disease (COPD) are the most common causes of hypoxemia, leading to secondary polycythemia. The degree to which laboratory markers of coagulation activation are elevated is substantially less in secondary polycythemia than in PV, 9 and there is no clear clinical evidence that secondary polycythemia poses an elevated thrombosis risk. Nevertheless, we have observed that cytoreduction with phlebotomy is frequently recommended for secondary polycythemia patients, likely extrapolating from the PV model.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA), obesity hypoventilation syndrome, and chronic obstructive pulmonary disease (COPD) are the most common causes of hypoxemia, leading to secondary polycythemia. The degree to which laboratory markers of coagulation activation are elevated is substantially less in secondary polycythemia than in PV, 9 and there is no clear clinical evidence that secondary polycythemia poses an elevated thrombosis risk. Nevertheless, we have observed that cytoreduction with phlebotomy is frequently recommended for secondary polycythemia patients, likely extrapolating from the PV model.…”
Section: Introductionmentioning
confidence: 99%
“…Because proinflammatory cytokines such as interleukin (IL)-1, IL-6, and tumor necrosis factor (TNF)-α are known to be elevated in SAP, [28][29][30] TF might be induced by monocytes/macrophages in response to these mediators or an endotoxin. 31,32 Furthermore, these mediators induce vascular endothelial injuries in SAP, and endothelial cells can induce TF. 33,34 In our study, however, plasma TF levels were not significantly correlated with serum levels of proinflammatory cytokines on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho and associates demonstrated in 12 of 17 patients with PV, low levels of factor XII, prekallikrein, and kallikrein inhibitor, suggesting that activation of the intrinsic coagulation system occurred in PV patients.&dquo; Kornberg and associates also confirmed that the coagulation system is activated by demonstrating that prothrombin fragmentl+2 levels, a peptide which is released when prothrombin is cleaved by factor Xa, were higher in PV. 17 However, the pathogenesis of activation of the blood coagulation system is unknown. To address this issue, Kornberg and colleagues also examined tissue factor levels and demonstrated a 17-fold increase in tissue factor (TF) generation in peripheral blood mononuclear cells stimulated by endotoxin from PV patients when compared to control subjects.17 The increase in TF levels was not due to increased platelet satellitism, which has been shown to occur in PV and other myeloproliferative disorders.…”
Section: Discussionmentioning
confidence: 99%